The Influence of the Work Environment, Organizational Commitment, and Information Technology on Employee Performance at KSP CU Dharma Prima Kita Yogyakarta - Andi, Andi; Kurniawan, Ignatius Soni (Perkumpulan Dosen Muda (PDM) Bengkulu, 2022)
This study aims to determine the effect of the work environment, organizational commitment, and information technology on employee performance. The population used in this study were employees of KSP CU Dharma Prima Â Kita, Yogyakarta. This research is a quantitative study and primary data was taken using a questionnaire on 40 respondents taken from a saturated population and the answers were processed using multiple linear regression analysis. The results in this study state that the work environment, organizational commitment, and information technology partially have a positive effect on employee performance.